Sequence Variants of BRCA1 and BRCA2 Genes in Four Iranian Families with Breast and Ovarian Cancer - F Keshavarzi; A Eskafi Noughani; MH Ayoubian; S Zeinali (Tehran University of Medical Sciences, 2011)
"nBackground: BRCA1 and BRCA2 genes have been recognized to be responsible for 20-30% of hereditary breast cancers and approximately 50% of familial breast and ovarian cancers. Therefore, the demand for BRCA1 and BRCA2 mutation screening is rapidly increasing as their identification will affect medical management of people at increased risk. Because of high costs involved in analysis of BRCA1 and 2 genes, contribution of different mutation types in BRCA1 and 2 and not knowing who should be tested has hampered wide spread use of molecular testing of high -risk families. There is a need to identify the genes and types of mutations involved in breast or ovarian cancers at different age of onsets and polymorphism and polymorphic variations in our population."nMethods: Twenty-seven patients with either early onset breast cancer (at age≤ 35 years) or a personal and/or family history of breast or ovarian cancer and 50 control subjects participated in this study. After collecting blood samples and extracting DNA, BRCA1 and BRCA2 genes were fully sequenced."nResults: Thirteen missense substitutions in BRCA1 and BRCA2 (9 and 4, respectively) were revealed. Two nucleotide substitutions were novel (Gly1140Ser in BRCA1 and Glu1391Gly in BRCA2). The Glu1038Pro and Gly1140Ser were found in large series of breast and ovarian cancer and matched controls."nConclusion: Some nucleotide substitutions were seen only in single families and other in several. In other cases, mutations were seen in both BRCA1 and BRCA2 genes. Clinical significance of these mutations was evaluated comparing with normal controls.